Perceived Coercion of Persons with Mental Illness Living in a Community - Lee, Min Hwa (Int J Environ Res Public Health, 2021)
Aims: The purpose of this study is to analyze the effect of the perceived coercion of people with mental illness living in a community on their therapeutic satisfaction and life satisfaction, mediated by therapeutic relationships. Methods: We evaluated several clinical variables (symptoms, psychosocial functioning, and insight), levels of perceived coercion, therapeutic relationships, therapeutic satisfaction, and life satisfaction in 185 people with mental illness (Mean age = 47.99, standard deviation (SD) = 12.72, male 53.0%, female 45.9%) who live in the community and use community-based mental health programs. The data collected were analyzed to test the proposed hypotheses using structural equation modeling (SEM). Results: The correlation analysis of all variables showed that clinical variables had statistically significant correlations with therapeutic relationship, therapeutic satisfaction, and life satisfaction, but no significant correlation with perceived coercion. Furthermore, perceived coercion was found to have significant predictive power for treatment satisfaction and life satisfaction mediated by therapeutic relationship. Specifically, the lower the perceived coercion, the better the therapeutic relationship. This, in turn, has a positive effect on the therapeutic satisfaction and life satisfaction of participants. Conclusions: Based on these findings, we suggest strategies to minimize coercion in a community.